اهمية مقياس ABSالسلوك التوافقي في بناء برنامج تكفلي للأطفال من ذوي الإعاقة الذهنية - رقاد, زريقة (كلية العلوم الإجتماعية لجامعة مستغانم, 2024)
تهدف الدراسة إلى بناء برنامج تكفل لذوي الإعاقة الذهنية استنادا على مقياس Abs لقياس السلوك التكيفي، ولتحقيق أهداف الدراسة استخدمت الباحثة مجموعة من الأدوات وتمثلت في : اختبار الذكاء المصور، مقياس abs للسلوك التوافقي ولاختيار البرنامج المقترح اعتمدت الدراسة على المنهج التجريبي ذو التصميم شبه تجريبي لعينة خضعت لقياس قبلي وبعدي حيث أجريت الدراسة على حالة واحدة، تحققت فرضيات الدراسة حسب النتائج التي توصلت إليها الباحثة: • استخدام نتائج مقياس السلوك التكيفي في إعداد برامج علاجية. • توجد فروق بين قيم متوسطات الانحراف المعياري للقياس القبلي والبعدي في تطوير السلوكات التكيفية لدى الأطفال المعاقين ذهنيا. • توجد فروق بین قیم متوسطات الانحراف المعياري للقياس القبلي والبعدي في خفض السلوكات الاتكيفية لدى الأطفال المعاقين ذهنيا. وخلصت الدراسة أن البرنامج المقترح ساهم في خفض السلوكات السلبية وتعزيز الإيجابية منها .
دراسة ميدانية بجمعية مساعدة الطفال المعاقين ذهنيا حي بيبينيار مستغانم
The study aims to develop a program that ensures for individuals with intellectual disabilities based on the ABS scale for measuring adaptive behavior. To achieve the study's objectives, the researcher utilized a set of tools, which included: The Pictorial Intelligence Test, ABS Scale for Adaptive Behavior, and to test the proposed program, the study relied on a quasi-experimental approach with a design for a sample that underwent pre- and post-measurement. The study was conducted on a single case. The study's hypotheses were confirmed according to the results obtained by the researcher: • Using the results of the ABS scale for adaptive behavior in preparing therapeutic programs. • There are differences between the mean standard deviation values of the pre and post measurements in developing adaptive behaviors in children with intellectual disabilities. • There are differences between the mean standard deviation values of the pre and post measurements in reducing maladaptive behaviors in children with intellectual disabilities. The study concluded that the proposed program contributed to reducing negative behaviors and enhancing positive ones.
Keywords: الإعاقة الذهنية ، السلوك التكيفي، بناء برنامج تكفل; Intellectual Disability, Adaptive Behavior, Program Development.